Isotopic composition of serum zinc and copper in healthy children and children with autism spectrum disorder in North America - Miller, Kerri; Day, Patrick L.; Behl, Supriya; Stromback, Lindsay; Delgado, Adriana; Jannetto, Paul J.; Wieser, Michael E.; Mehta, Sunil Q.; Pandey, Mukesh K. (Frontiers in Molecular Neuroscience, 2023)
To better understand zinc and copper regulation and their involvement in various biochemical pathways as it relates to autism spectrum disorder (ASD), isotopic composition of serum zinc and copper were evaluated in both healthy children and children with ASD in North America. No significant difference in isotopic composition of serum zinc or copper with respect to healthy controls and ASD children were identified. However, the isotopic composition of serum copper in boys was found to be enriched in 65Cu in comparison to previously published healthy adult copper isotopic composition. Furthermore, in both boys and girls, the average isotopic composition of serum zinc is heavier than previously published healthy adult isotopic zinc composition. There was also a negative association between total zinc concentrations in serum and the zinc isotopic composition of serum in boys. Finally, children with heavier isotopic composition of copper also showed a high degree of variability in their zinc isotopic composition. While numerous studies have measured the isotopic composition of serum zinc and copper in adults, this is one of the first studies which measured the isotopic composition of serum copper and zinc in children, specifically those diagnosed with ASD. The results of this study showed that age and gender specific normal ranges of isotopic composition must be established to effectively use isotopic composition analysis in studying various diseases including ASD.